Steam Video Game Reviews Classifier - Gonzáles Usca, Luis Alberto (2024)
This paper leverages a dataset generously provided by the Steam community, encompassing over 37 millionuser recommendations for various video games. These meticulously cleaned and preprocessed data originateexclusively from the Steam Store, a platform for online downloadable content in the realm of video games. Theprimary objective of this study is to conduct a sentiment analysis of user comments within the Steam Store,discerning both negative and positive emotions. The dataset comprises three distinct subsets, and this studyfocuses exclusively on the recommendations dataset for its analysis.